A Hybrid Neural System to Study the Interplay between Economic Crisis and Workplace Accidents in Spain - Sonia Contreras; Miguel Manzanedo; Álvaro Herrero (Journal of Universal Computer Science, 2019)
Workplace accident rates are always a constant source of concern in different scenarios. On the other hand, different economic cycles modify employment indicators, thereby affecting both the health and the wellbeing of workers. In this study, a Hybrid Neural System is proposed to support the analysis of both workplace accidents and different macroeconomic variables. The application of exploratory projection and nonlinear autoregressive models allow us to recognize patterns and subsequently study the interplay between the two fields, providing valuable information, so that directors can take more informed management decisions.